1996
DOI: 10.1111/j.1365-2125.1996.tb00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Theophylline population pharmacokinetics from routine monitoring data in very premature infants with apnoea

Abstract: Theophylline is commonly used in neonatology for the treatment and prophylaxis of apnoea of prematurity, and during ventilator weaning. NONMEM was used to study the population pharmacokinetics of intravenous and oral theophylline from retrospective drug monitoring data in 82 premature neonates, weighing < 1500 g at birth, and 5 32 weeks gestational age.Clearance (CL), volume of distribution (V), and oral bioavailability (Fl) from liquid preparations were modelled alone, and under the influence of demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 20 publications
2
28
1
Order By: Relevance
“…These results supported the fact that in parametric population modeling the fixed effects parameters are usually estimated with better precision than random effects parameters, except when there are very large numbers of subjects. 9,13 An important aspect of this study, often neglected in other population studies, was the independent assessment of the predictive performance in a subgroup of randomly selected infants who had similar characteristics to the index group but whose data were not used to develop the models. A confidence limit analysis indicated that there was a small, statistically insignificant bias of 3 mg/L among pairs of observed and model-predicted serum amoxicillin concentrations, the latter having been obtained by posthoc Bayesian forecasting in NONMEM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results supported the fact that in parametric population modeling the fixed effects parameters are usually estimated with better precision than random effects parameters, except when there are very large numbers of subjects. 9,13 An important aspect of this study, often neglected in other population studies, was the independent assessment of the predictive performance in a subgroup of randomly selected infants who had similar characteristics to the index group but whose data were not used to develop the models. A confidence limit analysis indicated that there was a small, statistically insignificant bias of 3 mg/L among pairs of observed and model-predicted serum amoxicillin concentrations, the latter having been obtained by posthoc Bayesian forecasting in NONMEM.…”
Section: Discussionmentioning
confidence: 99%
“…9 Predictive performance was assessed in terms of bias (mean prediction error, ME) and precision (root mean square prediction error, RMSE) and the associated 95% confidence intervals. 9,14 A systematic deviation between pairs of predicted and observed measurements can be used to estimate bias by the ME statistic, whereas the RMSE estimates scatter or variability; the lower the value of the RMSE the smaller is the magnitude of the differences between pairs of measurements.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of the wellknown immaturity of this metabolic pathway in neonates, one would expect both a reduced clearance of cisapride in neonates and a progressive increase in this parameter with postnatal age [27,28,29]. Cisapride concentrations obtained in our patients were very similar to those expected in adults receiving 10 mg three times a day, i.e., 20-40 ng/mL before and 50-100 ng/mL 1-2 h after drug intake [17], suggesting that the dosage regimen currently used in neonates is safe.…”
Section: Discussionmentioning
confidence: 98%